Seasonal surface circulation of southern South China Sea from multi-mission satellite altimetry - Muhammad Faiz Pa'suya, 1986-; Kamaludin Mohd. Omar, supervisor; Peter, Benny N., supervisor; Fakulti Geoinformasi dan Harta Tanah (2013)
Thesis (Sarjana Sains (Kejuruteraan Geomatik)) - Universiti Teknologi Malaysia, 2013